The Potential Of Superoxide Dismutase Enzyme From Tomato Fruit (Solanum Lycopersicum) To Repair Collagen Damage In 3t3 Fibroblast Cells Exposed To Ultraviolet A Radiation - Rosliana Patandung; Ana Indrayati; Jason Merari P (Eduvest - Journal of Universal Studies, 2024)
UV A radiation can cause photoaging to the skin which is show by a decrease in the amount of collagen and death of fibroblast cell. This study aimed to determine the SOD enzyme activity of tomatoes (Solanum lycopersycum Mill.) influences the increase of viability of fibroblast cell and deposition of collagen. The study design used a completely randomized design (CRD) with 11 treatments and 3 repetitions. The procedures of this study include: (1) extracting SOD enzymes (2) making bradford reagents (3) making standard protein solutions (4) measuring total protein content (5) testing the antioxidant activity of SOD enzymes (6) preparing 3T3 fibroblast cells (7) Cell exposure 3T3 fibroblasts with UV A rays (8) preparation of tomato SOD enzyme stock solutions (9) determination of cell viability and collagen deposition. Data analized by normality test, homogeneity test, one way ANOVA test, tuckey test and dunnet test. The results of SOD enzyme activity showed the highest percent inhibition was 77.83%. Highest value of percent viability of fibroblast cells that were exposed to UV A rays after given 90% SOD enzyme treatment was 233.00% and collagen deposition was 157.67%. The results showed that variations in the SOD enzyme concentration of tomatoes had a significant effect on cell viability and collagen deposition in fibroblast cells. with a value of sig = 0,000 (p <α). Based on the result, we can concluded that SOD enzyme from tomatoe fruit show significant activity as anti-photoaging.